Wisdom of Building a Clay House for Living in Maha Sarakham Province - Laoakka, Sastra (Journal of Cultural Approach, 2021)
This research aimed to 1) study the history of the wisdom of building a clay house for living, and 2) study the current conditions on the wisdom of building a clay house for living. The study was qualitative research and divided the sampling into 3 groups: (1) Key informants, (2) Stakeholders/Operators, and (3) Individuals, a total of 30 people. Data were collected from documents, preliminary fieldwork, structured and unstructured interviews, participation and non-participation observation, and focus group. The study found that 1) history began when Chinese people were populated by trade and brought the style of building houses into Maha Sarakham City. The building is popularly created as a single-layer fixed floor. A clay-brick wall-generating will connect “Lao Teng” or the mezzanine to store products. 2) The clay house is still seen on Nakhon Sawan Road, Maha Sarakham province, but in the early days, the construction of residences and shops was made of clay bricks that mixed with rice husk, sand, and chopped straws. Then, it is packed into a wooden size 12” x 6” x 41” and taken to dry with sunbathing 2 – 3 times. In conclusion, building a clay house in the present is to regain the traditional knowledge of the north-eastern antecedents and combine modern knowledge. The beginning of building clay houses is to create eco-friendly housing, reduce the destruction of nature, and help the homeless to have a durable and permanent home.